2019
DOI: 10.5194/bg-16-1675-2019
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterization of an aspen (<i>Populus tremuloides</i>) leaf litter sample that maintained ice nucleation activity for 48 years

Abstract: Abstract. Decaying vegetation was determined to be a potentially important source of atmospheric ice nucleation particles (INPs) in the early 1970s. The bacterium Pseudomonas syringae was the first microorganism with ice nucleation activity (INA) isolated from decaying leaf litter in 1974. However, the ice nucleation characteristics of P. syringae are not compatible with the characteristics of leaf litter-derived INPs since the latter were found to be sub-micron in size, while INA of P. syringae depends on muc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
(57 reference statements)
1
10
0
Order By: Relevance
“…Through strong winds at the ground level, INMs could be aerosolized through abrasive dislodgment and transported further. Another pathway would be that the aqueous INM extracts on the ground form a liquid film and get aerosolized during the mechanical impact of following rain droplets, similar to the bioaerosol generation mechanism suggested by Joung et al 2017, Wang et al (2016) and Kim et al (2020). Thereafter, splashinduced aerosol can be transported further during turbulent wind events and convection.…”
Section: Discussionmentioning
confidence: 86%
“…Through strong winds at the ground level, INMs could be aerosolized through abrasive dislodgment and transported further. Another pathway would be that the aqueous INM extracts on the ground form a liquid film and get aerosolized during the mechanical impact of following rain droplets, similar to the bioaerosol generation mechanism suggested by Joung et al 2017, Wang et al (2016) and Kim et al (2020). Thereafter, splashinduced aerosol can be transported further during turbulent wind events and convection.…”
Section: Discussionmentioning
confidence: 86%
“…INPs have been sampled in clouds and precipitation for decades (e.g., Rogers et al, 1998;Vali, 1971Vali, , 1966 to measure abundances, probe their compositions and investigate the extent to which they impact the properties of clouds. There are several caveats to consider when inferring in-cloud INP concentrations or properties from precipitation samples (Petters and Wright, 2015), including sweep-out of additional INPs as the hydrometeor traverses the atmosphere below the cloud (Vali, 1974) and heterogeneous chemistry due to adsorption or absorption of gases (Hegg and Hobbs, 1982;Kulmala et al, 1997;Lim et al, 2010). However, assessing the composition of INPs in precipitation samples is more straightforward than cloud particles.…”
mentioning
confidence: 99%
“…Storage protocols vary widely, including total storage time; time between collection and storage; and temperature fluctuations between collection, shipment and storage (if these details are provided at all; see summary Table S1 in the Supplement). Storage temperatures range from −80 • C (Vali et al, 1971) to +4 • C (e.g., Petters and Wright, 2015;Failor et al, 2017;Joyce et al, 2019), yet generally samples are stored between +4 and −20 • C. Reported storage intervals range between hours (Schnell et al, 1977;Christner et al, 2008) to 48 years (Vasebi et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, decayed leaf litter was found to be a potent source for INPs (Conen et al, 2016;Conen et al, 2017;Schnell and Vali, 1973), some of which may be stable for almost 50 years (Vasebi et al, 2019). Conen et al (2017) found that the emission of these INPs (active at temperatures above -8°C) increases in autumn and it is hypothesized that the vegetation could contribute to local climate.…”
Section: Introductionmentioning
confidence: 99%